miRs-134 and -370 function as tumor suppressors in colorectal cancer by independently suppressing EGFR and PI3K signalling - El-Daly, Sherien M.; Abba, Mohammed L.; Patil, Nitin; Allgayer, Heike (Scientific reports, 2016)
Growth factor receptor signalling plays a central and critical role in colorectal cancer. Most importantly, the EGFR signalling cascade involving PI3K/AKT/mTOR and Raf/MEK/ERK pathways are particularly relevant, since they are commonly activated in several cancer entities, including colorectal cancer. In this study, we show that miRs-134 and -370 are both capable of regulating these pathways by targeting EGFR and PIK3CA. In three different colorectal cancer cell lines (DLD1, HCT-116 and RKO), suppression of EGFR and PIK3CA through the enhanced expression of miR-134 or -370 led to a suppression of the key molecules of the PI3K/AKT/mTOR pathway. Furthermore, overexpression of miR-134 or -370 resulted in a significant reduction of cell proliferation, colony formation, migration, invasion and in-vivo tumor growth and metastasis. Concurrent experiments with small interfering RNAs targeting the prime targets show that our selected miRNAs exert a greater functional influence and affect more downstream molecules than is seen with silencing of the individual proteins. Taken together, these data indicate that miRs-134 and -370 are potential tumour suppressor miRNAs and could play a fundamental role in suppressing colorectal cancer tumorigenesis through their ability to co-ordinately regulate EGFR signalling cascade by independently targeting EGFR and PIK3CA.